Implementation Of Open Source Security Information Management (OSSIM) On Security Computer Network - Putra, Angga Ardian; Sapri, Sapri; Akbar , Abdussalam Al (Jurnal Komputer, 2022)
This research is entitled APPLICATION OF Open Source Security Information Management (OSSIM) in Computer Network Security. Which aims to build a system that can monitor and monitor computer network security at SMA Negeri 1 Seluma. Where in monitoring and network security an Open Source Security Information Management (OSSIM) system is used which utilizes kibana and security uses Squert using the Linux Ubuntu Server 20.04 operating system. In monitoring the network, Kibana can monitor computer network activities properly including monitoring activities based on the service used, from the results of this monitoring which if there are activities that are not allowed such as opening gambling sites and others, security or blocking of squert will be carried out. Overall the monitoring and security system is running well. Linux operating system ubuntu server 20.04 is very good at running kibana and squert to monitor and monitor computer network security at SMA N 1 Seluma.